Prostaglandins and Platelet Aggregation in Vivo - Kloeze, J (Thrombosis and Haemostasis, 1970)
Prostaglandins E1 and ω-homo-E1 which were shown previously to inhibit adenosine diphosphate (ADP)-induced platelet aggregation in vitro have now been found to inhibit this process also in vivo. Both prostaglandins inhibit transient thrombocytopenia induced by intravenous injection of ADP; PGE1 increases also the LD 50 of ADP when injected in high amounts into young rats. In both cases platelet aggregation in vivo is the primary cause of the phenomena observed.The symptoms observed on overdosing ADP by intravenous injection are unconsciousness within 10-20 sec after completion of the injection immediately followed by respiratory arrest and eventual death of the animal, generally within 10 min. It seems that blocking of the supply of blood to the brain by platelet thrombi, which on histological examination were found to occlude blood vessels in different organs, is the most important causative factor of the symptoms observed.